Transposable element variants and their potential adaptive impact in urban populations of the malaria vector Anopheles coluzzii - Vargas-Chavez, Carlos; Longo Pendy, Neil Michel; Nsango, Sandrine E.; Aguilera, Laura; Ayala, Diego; González, Josefa (Genome Research, 2022)
Anopheles coluzzii is one of the primary vectors of human malaria in sub-Saharan Africa. Recently, it has spread into the main cities of Central Africa threatening vector control programs. The adaptation of An. coluzzii to urban environments partly results from an increased tolerance to organic pollution and insecticides. Some of the molecular mechanisms for ecological adaptation are known, but the role of transposable elements (TEs) in the adaptive processes of this species has not been studied yet. As a first step toward assessing the role of TEs in rapid urban adaptation, we sequenced using long reads six An. coluzzii genomes from natural breeding sites in two major Central Africa cities. We de novo annotated TEs in these genomes and in an additional high-quality An. coluzzii genome, and we identified 64 new TE families. TEs were nonrandomly distributed throughout the genome with significant differences in the number of insertions of several superfamilies across the studied genomes. We identified seven putatively active families with insertions near genes with functions related to vectorial capacity, and several TEs that may provide promoter and transcription factor binding sites to insecticide resistance and immune-related genes. Overall, the analysis of multiple high-quality genomes allowed us to generate the most comprehensive TE annotation in this species to date and identify several TE insertions that could potentially impact both genome architecture and the regulation of functionally relevant genes. These results provide a basis for future studies of the impact of TEs on the biology of An. coluzzii.
10.1101/gr.275761.121